(untitled) (Economics and region, 2022)
The purpose of this work is to study the trends in the development of knowledge management; analysis of features and conditions of functioning of the knowledge management system. In the research process, the statistical method of scientific knowledge, systematic and complex approaches to the study of theoretical aspects of knowledge management, as well as methods of graphic representation, generalization method and formal-logical method were applied. The work explores the concept of knowledge management and its components, which include explicit and latent knowledge. It was established that knowledge management is a process of creation, distribution and use of organizational knowledge within the organization in order to ensure competitiveness, stability of activity and economic development in the conditions of a globalized competitive economy. It was found that latent knowledge is personal, unexpressed knowledge possessed by a person. Latent knowledge is generated mainly as a result of gaining experience. Explicit knowledge is generated by embodying latent knowledge in material carriers (artifacts). It is also determined that the main obstacles to the transfer of knowledge among the organization’s employees are: the recipient’s inability to perceive knowledge; lack of knowledge about production factors involved in practice; lack of understanding by the recipient of knowledge of the organizational context in which this practice will be applied; lack of understanding between the giver and recipient of knowledge; lack of motivation to share knowledge; lack of transparency in information networks of knowledge and imperfection of "information architectures" (taxonomies, ontologies); insufficient integration of tasks into business processes, etc.The task of the state in the context of the formation of the knowledge management system is to expand the availability of quality higher and post-graduate education, as well as specific programs leading to the acquisition of scientific degrees, the implementation of policies and programs based on measures that stimulate the development of innovative activities and the formation of new explicit knowledge of society . The obtained research results can be useful in the formation of the human capital management strategy, as well as personnel strategies of organizations.